Sequestosome 1/p62-related pathways as therapeutic targets in hepatocellular carcinoma. (4th May 2019) - Denk, Helmut; Stumptner, Conny; Abuja, Peter M.; Zatloukal, Kurt
ABSTRACT: Introduction : Protein sequestosome 1/p62 (p62) plays a crucial role in vital complex and interacting signaling pathways in normal and neoplastic cells. P62 is involved in autophagy, defense against oxidative stress via activation of the Keap1/Nrf2 system, in protein aggregation and sequestration, and in apoptosis. Autophagy contributes to cell survival and proliferation by eliminating damaged organelles, potentially toxic protein aggregates and invading microorganisms, and by providing nutrients under starvation conditions. The same holds true for oxidative stress defense, which may prevent genomic alterations and tumor initiation but also protect established tumor cells and promote tumor progression. Cross-talk between autophagy and apoptosis is regulated by a signaling network with the involvement of p62. Areas covered : The review deals with structure, function, and regulation of p62 and its role in liver carcinogenesis. Emphasis is placed on mechanisms leading to overexpression of p62 and its accumulation as inclusion bodies in HCC and on the impact of p62-dependent signaling pathways in tumor cells with the aim to explore the possible role of p62 as the therapeutic target. Expert opinion : Depending on the context, targeting p62 or interference with related pathways, such as autophagy, is a potential therapeutic strategy in HCC. However, the heterogeneity of this tumor entity and the complexity and mutual interactions of the p62-dependent pathways involved are challenges for a targeted therapy since interference with p62-mediated regulatory processes could result likewise in inhibition of tumorigenesis and in its promotion and thus provoke harmful side effects. Therapy-related patient stratification based on reliable markers to better define pathogenic principles of the tumor is a necessity when this type of treatment is considered.